2020
DOI: 10.1186/s12864-020-07236-z
|View full text |Cite
|
Sign up to set email alerts
|

Initial response of ovarian tissue transcriptome to vitrification or microwave-assisted dehydration in the domestic cat model

Abstract: Background Long term preservation of living ovarian tissues is a critical approach in human reproductive medicine as well as in the conservation of rare animal genotypes. Compared to single cell preservation, optimization of protocols for tissues is highly complex because of the diversity of cells responding differently to non-physiological conditions. Using the prepubertal domestic cat as a model, the objective was to study immediate effects of vitrification or microwave-assisted dehydration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 70 publications
(98 reference statements)
0
21
0
Order By: Relevance
“…Thus, getting information on the whole transcriptome changes in the tissue during preservation is essential for understanding the mechanisms of stress response and recovery of cells as a system. For instance, our group recently demonstrated how RNA-seq and resulting functional networks can help to understand the response of ovarian tissue to various stresses caused by preservation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, getting information on the whole transcriptome changes in the tissue during preservation is essential for understanding the mechanisms of stress response and recovery of cells as a system. For instance, our group recently demonstrated how RNA-seq and resulting functional networks can help to understand the response of ovarian tissue to various stresses caused by preservation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, NOTCH2 has been shown to be a direct target of miR-34c with its expression greatly decreased in miR34c transfected cells (Bouhallier et al, 2010). In our study, NOTCH2 paralog NOTCH1 has been predicted as a DE target of several miRNAs from the major cluster, including miR-34b-3p, miR-34c-5p, miR-146a-5p, miR-200c-3p, miR-449-5p, and miR-92b-3p. Tissue preservation protocols, such as vitrification, slowfreezing and recently developed microwave-assisted dehydration, expose cells to non-physiological conditions which may disturb cellular homeostasis and lead to cellular Frontiers in Genetics frontiersin.org stress (Lee et al, 2019;Amelkina and Comizzoli, 2020). Protocols are constantly being optimized to reduce the severity of cellular stress and mitigate any potential damage to proteins, DNA, RNA, and lipids.…”
Section: Discussionmentioning
confidence: 99%
“…It is also an important biomedical model, carrying a similarity with human genome with high degree of conserved synteny and serving as a model for ∼250 genetic diseases that are analogous to human disorders ( O’Brien et al, 2002 ; Pontius et al, 2007 ; Tamazian et al, 2014 ). Recently, our group has been focusing on elucidating transcriptome dynamics in the ovarian and testicular tissue of domestic cat to better understand molecular mechanisms behind gonadal development and response of tissues to stress caused by preservation protocols ( Amelkina and Comizzoli, 2020 ; Amelkina et al, 2021 ). We have reported major changes in mRNA expression in the ovarian tissue in response to vitrification and microwave-assisted preservation ( Amelkina and Comizzoli, 2020 ), as well as gradual shifts in transcriptome dynamics throughout testicular development ( Amelkina et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of applying this drying technique to gonadal tissue has also been explored. Drying of cat ovarian tissue showed limited impact on morphology but altered transcriptional activity and gene expression , Amelkina & Comizzoli 2020. Recently, drying of cat testicular tissues showed that structural integrity and cell viability could be maintained at an acceptable level (Silva et al 2020).…”
Section: Dehydration Methods and Storage Options For Germplasmsmentioning
confidence: 99%